Association of prior opium addiction with incident non-alcoholic fatty liver disease: A case-control study. - Sina Bazmi; Talieh Parvaneh; Zahra Mohammadi; Parisa Pishdad; Mehrnaz Ghaedian; Azizallah Dehghan; Reza Homayounfar; Mojtaba Farjam (PLoS ONE)
Background Non-alcoholic fatty liver disease (NAFLD) is a prevalent chronic liver condition with no approved pharmacological treatments. Given opium's potential metabolic effects on lipid profiles, blood pressure, and glucose levels, factors known to influence NAFLD, we hypothesized that opium addiction might be inversely associated with NAFLD risk. Objective To investigate the association between opium addiction during a six-year period (2016-2022) and the subsequent incidence and severity of NAFLD in 2022 among participants of the Fasa Adult Cohort Study (FACS). Methods Adults aged 35-70 were selected from the FACS baseline dataset (2016) after excluding individuals with NAFLD (based on the Fatty Liver Index and regional cutoffs), obesity, cancer, chronic liver diseases, or regular alcohol use. Of 550 randomly selected participants invited for sonography in 2022, 396 attended; 170 were newly diagnosed with NAFLD. Cases and controls were matched 1:1 using SPSS based on age, sex, diabetes, and hyperlipidemia. Opium addiction was defined using DSM-5 criteria via structured interviews, while NAFLD diagnosis and grading were performed using blinded ultrasound assessment. Fisher's exact and Fisher-Freeman-Halton tests were used for analysis. A post hoc power analysis was also conducted. Results The final analysis included 206 participants (103 cases, 103 controls). Opium addiction was observed in 31 NAFLD cases and 72 controls, a non-significant difference. However, the prevalence of opium addiction differed significantly across NAFLD severity grades. The post hoc statistical power was estimated at 60%. Conclusion Although not statistically significant, fewer opium addicts developed NAFLD than non-addicts. This inverse trend, along with significant variation across NAFLD grades, suggests a possible association that warrants further investigation. Larger studies are needed to explore this potential relationship. If confirmed, opioid-based therapies may offer dual benefits for managing chronic pain and metabolic risk in selected NAFLD populations.